Determination of the estrous cycle phases of rats: some helpful considerations - MARCONDES F. K. (Brazilian Journal of Biology, 2002)
The short length of the estrous cycle of rats makes them ideal for investigation of changes occurring during the reproductive cycle. The estrous cycle lasts four days and is characterized as: proestrus, estrus, metestrus and diestrus, which may be determined according to the cell types observed in the vaginal smear. Since the collection of vaginal secretion and the use of stained material generally takes some time, the aim of the present work was to provide researchers with some helpful considerations about the determination of the rat estrous cycle phases in a fast and practical way. Vaginal secretion of thirty female rats was collected every morning during a month and unstained native material was observed using the microscope without the aid of the condenser lens. Using the 10 x objective lens, it was easier to analyze the proportion among the three cellular types, which are present in the vaginal smear. Using the 40 x objective lens, it is easier to recognize each one of these cellular types. The collection of vaginal lavage from the animals, the observation of the material, in the microscope, and the determination of the estrous cycle phase of all the thirty female rats took 15-20 minutes.